Global insights: navigating universality with UiTM Pulau Pinang / Noorsuhada Md Nor - Md Nor, Noorsuhada (UiTM Global @ Office of International Affairs, 2024)
The edition showcases the dedicated efforts of UiTM Pulau Pinang staff and students to uphold the university’s vision of becoming a globally renowned institution by 2025 (GRU2025).